Welcome the Diaspora: Slave Trade Heritage Tourism and the Public Memory of Slavery - Araujo, Ana (Ethnologies, 2010)
This article examines the emergence of the public memory of slavery and the Atlantic slave trade in the Republic of Benin, by explaining how the heritagization of slavery was crucial for the development of a local tourism industry. The article shows that the rise of the public memory of the Atlantic slave trade in Benin is not an isolated venture and that similar initiatives were also developed in other West African countries. The article also discusses how the plural memories of slavery are articulated with the expectations of African American and Afro-Caribbean tourists, who are the main target of projects focusing on slavery cultural heritage and roots tourism. The article concludes that although slavery heritage tourism helped to place Benin among the international slavery tourist destinations, it also contributed to make visible the plural memories of slavery and to commodify African tangible and intangible heritage.